2020
DOI: 10.1108/sasbe-08-2019-0115
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort prediction of air-conditioned and passively cooled engineering testing centres in a higher educational institution using CFD

Abstract: PurposeThe purpose of this paper is to analyse the thermal environment of two engineering testing centres cooled via different means using computational fluid dynamics (CFD), focussing on the indoor temperature and air movement. This computational technique has been used in the analysis of thermal environment in buildings where the profiles of thermal comfort parameters, such as air temperature and velocity, are studied.Design/methodology/approachA pilot survey was conducted at two engineering testing centres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Meanwhile, according to Liu et al (2019), there is no simple system to describe information content requirements, specification for thermal comfort management practices and information exchanges in construction projects. The integration of thermal comfort parameter information deliveries into a project plan contents of unclear understanding methods of energy efficiency and indoor wellbeing technologies, for instance, control systems, lighting, ventilation, thermal storage and heat recovery, which include temperature differences between indoors and outdoors, building envelope and the efficiency of heating and cooling equipment for thermal industry standardisation (Galagoda et al , 2018; Kwong et al , 2020). The building's thermal system performance in construction activities can be optimised through the deployment of more sophisticated or innovative modelling tools and sensor data visualisation techniques.…”
Section: Thermal Comfort Optimisation (Iot–bim) Practices In Pc Build...mentioning
confidence: 99%
“…Meanwhile, according to Liu et al (2019), there is no simple system to describe information content requirements, specification for thermal comfort management practices and information exchanges in construction projects. The integration of thermal comfort parameter information deliveries into a project plan contents of unclear understanding methods of energy efficiency and indoor wellbeing technologies, for instance, control systems, lighting, ventilation, thermal storage and heat recovery, which include temperature differences between indoors and outdoors, building envelope and the efficiency of heating and cooling equipment for thermal industry standardisation (Galagoda et al , 2018; Kwong et al , 2020). The building's thermal system performance in construction activities can be optimised through the deployment of more sophisticated or innovative modelling tools and sensor data visualisation techniques.…”
Section: Thermal Comfort Optimisation (Iot–bim) Practices In Pc Build...mentioning
confidence: 99%
“…Rather, Amin et al (2015) showed the unacceptable thermal conditions in three building of a laboratory that were facilitated with an air conditioning system. Kwong et al (2020) through an experiment on CFD software found the air temperature in both the laboratory and workshop did not comply with the MS 1525 standard, though at a low metabolic rate of 1.0 met. Past findings presented the issues of thermal comfort in educational buildings, focusing on labs and workshop users that are exposed to the sick building syndrome (SBS) symptoms, which lead to psychological and physiological effects (N. D. Amin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, Amin et al, showed the unacceptable thermal conditions in three building of a laboratory that were facilitated with an air conditioning system. Kwong et al, [9] through an experiment on CFD software found the air temperature in both the laboratory and workshop did not comply with the MS 1525 standard, though at a low metabolic rate of 1.0 met. Past findings presented the issues of thermal comfort in educational buildings, focusing on labs and workshop users that are exposed to the sick building syndrome (SBS) symptoms, which lead to psychological and physiological effects [12].…”
Section: Introductionmentioning
confidence: 99%